Prenatal AD.VEGF gene therapy increases fetal growth velocity and alters uterine artery vascular reactivity in the absence of a measurable effect on uterine blood flow in a sheep model of fetal growth restriction. (18th April 2012) - Carr, DJ; Aitken, RP; Milne, JS; Mehta, V; Peebles, DM; Martin, JF; Zachary, IC; Wallace, JM; David, AL
Abstract : Introduction: Adenovirus (Ad) mediated over-expression of vascular endothelial growth factor (VEGF) in the uterine artery (UtA) enhances pre- and postnatal growth in growth-restricted sheep fetuses (Carr 2011a/2011b). Herein effects on uterine blood flow (UBF), vascular reactivity and UtA remodelling were investigated. Methods: Singleton pregnancies were established by embryo transfer in 57 adolescent ewes subsequently overnourished to restrict placental/fetal growth or fed a control diet. At 89±1.5d gestation, overnourished ewes were randomised to receive Ad.VEGF-A165 (n=18), Ad.LacZ (n=14) or saline (n=13) injected into each UtA. Controls received saline (n=12). Flowprobes were fitted around the UtA supplying the gravid horn. Fetal biometry/wellbeing was assessed blind by weekly ultrasound. UBF was monitored until necropsy at 131±1.6d. In 24 animals, three branches of UtA from both the gravid and non-gravid horns were challenged in an organ bath with phenylephrine and bradykinin to assess vessel contractility and relaxation, respectively. Adventitial vessels were immunostained with anti-vWF and counted. Intima:media ratios (IMR) were also calculated. Results: Fetal abdominal circumference measurements were greater in Ad.VEGF-A165 versus Ad.LacZ/saline groups at 112±0.1d and 119±0.1d gestation (p=<0.001–0.047) but Ad.VEGF-A165 had no measurable effect on UBF or UtA adventitial vessel number. IMR was greater in Ad.VEGF-A165 versus Ad.LacZ+saline groups in the main gravid UtA branch (p=0.016). Bradykinin-induced relaxation was increased in Ad.VEGF-A165 versus Ad.LacZ/saline/control groups in the second gravid UtA branch (p=0.001–0.032). Conclusion: Ad.VEGF-A165 increased fetal growth velocity without apparent changes in UBF. There was evidence of enhanced vasodilatation and increased IMR but no neovascularisation in UtAs treated with Ad.VEGF-A165 .